Soft City : Building density for everyday life - Sim, David, ....- (Washington : Island Press, 2019)
Soft City begins with the big ideas of happiness and quality of life, and then shows how they are tied to the way we live. The heart of the book is highly visual and shows the building blocks for neighborhoods: building types and their organization and orientation; how we can get along as we get around a city; and living with the weather. As every citizen deals with the reality of a changing climate, Soft City explores how the built environment can adapt and respond. Soft City offers inspiration, ideas, and guidance for anyone interested in city building. Sim shows how to make any city more efficient, more livable, and better connected to the environment.
Keywords: Architectuur; Duurzame Stedenbouw; Stadsontwikkeling; Stadsvernieuwing